End-stage renal failure in type 2 diabetes: a medical catastrophe of worldwide dimensions - Ritz, Eberhard; Rychlik, Ivan; Locatelli, Francesco; Halimi, Serge (American journal of kidney diseases, 1999)
The incidence of patients with end-stage renal failure and diabetes mellitus type 2 as a comorbid condition has increased progressively in the past decades, first in the United States and Japan, but subsequently in all countries with a western lifestyle. Although there are explanations for this increase, the major factor is presumably diminishing mortality from hypertension and cardiovascular causes, so that patients survive long enough to develop nephropathy and end-stage renal failure. This review summarizes the striking differences between countries against the background of a similar tendency of an increasing incidence in all countries. Survival on renal replacement therapy continues to be substantially worse for patients with type 2 diabetes. A major reason for this observation is that patients enter renal replacement programs with cardiovascular morbidity acquired in the preterminal phase of renal failure. It is argued that the challenge for the future will be better patient management in earlier phases of diabetic nephropathy to attenuate or prevent progression, as well as cardiovascular complications.